A review on recent developments in hydrodynamic cavitation and advanced oxidative processes for pretreatment of lignocellulosic materials. (February 2022) - Prado, C.A.; Antunes, F.A.F.; Rocha, T.M.; Sánchez-Muñoz, S.; Barbosa, F.G.; Terán-Hilares, R.; Cruz-Santos, M.M.; Arruda, G.L.; da Silva, S.S.; Santos, J.C.
Graphical abstract: Highlights: AOPs/HC technologies can decrease the chemical inputs in biomass pretreatment. Novel technologies such AOPs and HC promote high saccharification rate of biomass. AOPs and HC advantages include shorter time and mild process conditions. HC pretreatment favors short-time, versatile and continuous process. Combined AOPs and HC provides potential scaling up scenario for biorefineries. Abstract: Environmental problems due to utilization of fossil-derived materials for energy and chemical generation has prompted the use of renewable alternative sources, such as lignocellulose biomass (LB). Indeed, the production of biomolecules and biofuels from LB is among the most important current research topics aiming to development a sustainable bioeconomy. Yet, the industrial use of LB is limited by the recalcitrance of biomass, which impairs the hydrolysis of the carbohydrate fractions. Hydrodynamic cavitation (HC) and Advanced Oxidative Processes (AOPs) has been proposed as innovative pretreatment strategies aiming to reduce process time and chemical inputs. Therefore, the underlying mechanisms, procedural strategies, influence on biomass structure, and research gaps were critically discussed in this review. The performed discussion can contribute to future developments, giving a wide overview of the main involved aspects.